MEMAYU HAYUNING BAWANA: MEMAHAMI ESENSI GOTONG ROYONG DALAM NILAI KEARIFAN LOKAL MASYARAKAT JAWA - Noorzeha, Fuad; Lasiyo (Sanjiwani: Jurnal Filsafat, 2023)
The view that humans are social creatures has now shifted to anti-social humans. Technological advances make humans abandon direct interaction in social life. The presence of technology also makes social relations between individuals and communities replaced with wireless networks. The role of parents in educating children has also changed. Although social interaction is now becoming easier and instantaneous, there is no essence of social interaction itself. Gotong Royong is one of the alternative activities that need to be preserved by the community To improve human status as social creatures. In addition, these activities can foster togetherness in building the sustainability of micro cosmos and macro cosmos in human life in the world.  The purpose of this study is to affirm the function and benefits of Gotong Royong in human experience through awareness of the saying "Memayu Hayuning Bawana" for Javanese people. This research is literature research using a phenomenological approach to the social life of the community towards mutual aid activities. The result of this study is to understand the essence of the spirit of mutual assistance so that society can put aside the ego of each individual to achieve better social goals. In addition, it can be aligned with the value of local wisdom "Memayu Hayuning Bawana" which is still maintained by some Javanese people to this day, especially village communities. This philosophy of life has been used as a guide and practice in preserving nature, preserving the environment, and harmony among humans. The saying is used as the spiritual path of the Javanese people.